AKIBAT HUKUM PEMUTUSAN HUBUNGAN KERJA YANG DILAKUKAN OLEH PENGUSAHA SEBELUM BERAKHIRNYA PERJANJIAN KERJA (STUDI DI KANTOR DINAS TENAGA KERJA KABUPATEN ASAHAN) - Mangaraja Manurung; Urip Giyono; Rahdy Kurniawan (Jurnal De Jure Muhammadiyah Cirebon, 2022)
The working relationship between workers/laborers and employers is not always harmonious, there are many factors that cause disputes, for example a working relationship based on an employment agreement, also known as a work contract, is considered more efficient, because the employer can at will make the terms and conditions of work agreed upon as well. by workers. For example, it is agreed to work for two years with a certain wage for the type of work given by the employer. Another problem that often arises is the issue of unilaterally terminating the employment contract by the Employer and contrary to the provisions of the Manpower Act, thereby causing harm to the continuation of work for the worker; This type of research is juridical Empirical. This is done by researching directly to the research location, using a legal approach (approach), to see firsthand its implementation. and conduct interviews with officers from the Department of Manpower. With the formulation of the problem How is the supervision of the Manpower Office on the implementation of the employment relationship in the employment agreement made by the Company and the Workers / Laborers in Asahan Regency.? And what are the legal actions taken by the Department of Manpower for the Company that terminates the Worker/Labourer before the expiration of the Employment Agreement. Keywords: Legal consequences, Termination of Employment, Employment Agreement